(3eYQaI Ydhe GdMOjKs - (3GdMGce GdfjSGHhQj , eMeO Hf YHO Gddg Hf MeOhjg Hf fYje GdVHj GdWgeGfj GdfjSGHhQj, CHh YHO Gddg, GdMGce, GHf GdHjY,J (B405 (3g` s ((3YHO GdQMje Hf MeO Hf YHO GdQMje Hf GdegJQ GdfgGhfOi s)
(3ChdgG (B:s
(3bGd GdTjN GdMGce GdfjSGHhQi (B: (3GdMeO ddg Pi Gdef hGdEMSGf s
(3BNQgG (B:s
(3bGd EPG QLYJ aGcJHg hGNJeg hhLgg Hg Edi BNQ cJGH eYQaI CUhd GdMOjK s
(3GdhQbI GdChdi HNW MOjKs
(3HBNQ GdfSNI eYGQVI SfI (B551s
(3Ke SeGY Ydi CHj GdaJM eMeO Hf CMeO Hf HNJjGQ GdefOGFi SfI (B585s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs